2012
DOI: 10.1021/ef300894h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bioethanol Blended Diesel Fuel and Engine Load on Spray, Combustion, and Emissions Characteristics in a Compression Ignition Engine

Abstract: This study investigates the effect of engine load condition on the injection spray, combustion, and exhaust emissions characteristics of a diesel–bioethanol blended fuel diesel engine. In this study, the injection characteristics, such as the effective flow diameter and the effective flow velocity, were calculated from the nozzle flow model. The macroscopic spray characteristics of diesel–bioethanol fuels were measured and analyzed using a spray visualization system. Using a four-cylinder test engine with 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Only two studies in the literature were found in relation to surfacte tension of e-diesel. The exponential decrease of the surface tension from E0 to E25 in e-diesel was found by Li et al (24) The surface tension of e-diesel exponentially decreased with increase in bioethanol content up to 20% of bioethanol, and thereafter addition of bioethanol didn't affect the surface tension of e-diesel (29) . It should be pointed out that the exact value of surface tension for the same e-diesel was widely different from two studies, due to different surface tension of diesel tested in the experiment, respectively.…”
Section: E-diesel and E-biodiesel Blendsmentioning
confidence: 75%
See 3 more Smart Citations
“…Only two studies in the literature were found in relation to surfacte tension of e-diesel. The exponential decrease of the surface tension from E0 to E25 in e-diesel was found by Li et al (24) The surface tension of e-diesel exponentially decreased with increase in bioethanol content up to 20% of bioethanol, and thereafter addition of bioethanol didn't affect the surface tension of e-diesel (29) . It should be pointed out that the exact value of surface tension for the same e-diesel was widely different from two studies, due to different surface tension of diesel tested in the experiment, respectively.…”
Section: E-diesel and E-biodiesel Blendsmentioning
confidence: 75%
“…Density: Torres-Jimenez et al (28) found in the ediesel from 0 to 15% of ethanol that density of e-diesel was decreased with increase in bioethanol content. However, density values for all samples tested are within the standard range (limit of EN 590 Min / Max = 820 / 845 kg/m 3 at the reference temperature of 288 K. This means that there will be no problems related to atomization of e-diesel The measurement results by Park et al (29) showed that the density of ediesel with 10% of biodiesel (soybean oil methyl ester) as emulsifier generally decreased with the increase in bioethanol content from 0 to 50%. However, density values for more than 30% of bioethanol content are not within the standard range of EN 590.…”
Section: E-diesel and E-biodiesel Blendsmentioning
confidence: 79%
See 2 more Smart Citations
“…Heat release analysis is an important tool in the research of the combustion process in diesel engines. Theoretical heat release can be obtained through, for example, CFD models of the combustion, but here, the heat release is calculated from in-cylinder pressure measurements based on a single-zone combustion model. Following a heat release calculation, there are several methods to investigate the combustion process in the diesel engine.…”
Section: Heat Release Calculation From In-cylinder Measurements Based...mentioning
confidence: 99%